Dangers in the Desert: Jean Arasanayagamâ€™s â€œThe Sand Serpentsâ€ - Paul, The American College, Madurai, India, Premila (Asiatic: IIUM Journal of English Language and Literature, 2012)
This essay analyses Jean Arasanayagamâ€™s depiction of domestic labour abroad (through the consciousness of Nanda during a taxi ride) in â€œThe Sand Serpents.â€ Unlike the western dream, migration to the Middle East is a means of investment in Sri Lanka for a domestic help. The ultimate dream is to return home. The contrasting images of openness and constriction bring out Nandaâ€™s responses to homeland and desert land; success and failure. The renewed perspective of home privileges normalcy and routine over money and excitement. The essay discusses areas of collision between the workspace of a domestic maid and the private space of the employer that condition power relations and behaviour patterns. The language of communication is rendered irrelevant. Ultimately the story affirms Nandaâ€™s self-knowledge and rootedness in her own homeland.